“Meet de Boys on the Battlefront”: Festive Parades and the Struggle to Reclaim Public Spaces in Post-Katrina New Orleans - Aurélie Godet (European Journal of American Studies)
New Orleans has been the parading capital of the United States for close to two centuries. Since Hurricane Katrina, parades have become more important than ever, as many residents have called festive organizations home to reclaim urban space and say “We are New Orleans” or “This is our city.” This article will consider how the place-making practices of Mardi Gras Indian tribes, social aid and pleasure clubs, and carnival krewes have all reflected and informed citizens’ responses to displacement after Katrina. Drawing on Abdou Maliq Simon’s conceptualization of people as infrastructure and a series of three case studies, it will refocus the discussion on the rebuilding of the Crescent City around its citizens, taking the embodied festive practices of New Orleanians as a lens through which to examine the politicization of public space in post-Katrina New Orleans.